Trace metals in soils irrigated with waste water in a periurban area downstream Hanoi City, Vietnam - Bjuhr, Josef (SLU/Dept. of Soil Sciences, 2007)
The rapid urbanization and industrialisation in many South-East Asian countries has resulted in increasing amounts of untreated industrial and domestic waste water, which is discharged into rivers and lakes. The waste water is a highly complex and nutrient rich water solution used by the farmers for irrigation of their fields. It contains various potentially toxic elements including several trace metals. A better understanding of the irrigation systems used, and the distribution of the metals across arable fields is essential in order to reduce the environmental and health risks associated with the use of waste water.